Penerapan Problem Based Learning untuk Meningkatkan Hasil Belajar Mata Pelajaran Alat Industri Kimia - Usman Arief; Hasri Hasri; Ruhmah Ruhmah (Universitas Negeri Makassar, 2022)
Implementation of Problem Based Learning to improve Learning outcomes of Chemical Industry Equipments. This research is a class action study that aims to improve learning outcomes in the Chemical Industry Equipments course through the Problem Based Learning Model. The subject of this study is Students of Class XI Industrial Chemistry 1 SMK Negeri 1 Lumajang as many as 16 students. The methods used in discussion and with the scientific approach-TPACK. Data collection is done using observation and evaluation techniques at the end of learning at the end of each cycle. The results of this study show that: The average value of learning outcomes in Chemical Industry Equipments Students course Class XI Industrial Chemistry 1 SMK Negeri 1 Lumajang at the end of cycle I that is 43.13 with completion reached 31.25%, the average value of student learning outcomes in cycle II increased to 66 with completion reaching 68.75%, and in cycle III the average score reached the highest which is 87.5 and completion reached 93.75%. Problem Based Learning model can improve learning outcomes in Equipments of Chemical Industry course.